Delayed epidural pseudoaneurysm following cervical laminectomy and instrumentation in a patient with canal stenosis secondary to skeletal fluorosis: A case report. Issue 8 (February 2018) - Diao, Yinze; Sun, Yu; Wang, Shaobo; Zhang, Fengshan; Pan, Shengfa; Liu, Zhongjun
Abstract: Rationale: The typical intraoperative presentation of vertebral artery injury (VAI) usually involves profuse bleeding and requires immediate treatment. However, an occult VAI may occur intraoperatively and result in delayed life-threatening epidural pseudoaneurysm several days postoperatively. Patient concerns: A 21-year-old man with compressive cervical myelopathy resulting from canal stenosis of skeletal fluorosis underwent decompression of C1 to C7 and instrumentation from C2 to C7. No impressive bleeding event occurred during the operation. On postoperative day 40, progressive quadriplegia developed. Diagnoses: Pseudoaneurysm of the VA was established by angiography. Interventions: After occlusion of the right VA, the patient underwent hematoma clearing. Outcomes: Fortunately, the patient experienced significant recovery of neurologic function after the second surgery. Lessons: From this case, we realize even in the absence of obvious signs of VAI during a cervical operation, postoperative evaluation should be mandatory for suspected bleeding events occurring at VAI-prone sites during surgery. Moreover, the bone morphological abnormality of skeletal fluorosis was determined to be the most important risk contributing to VAI in this case. The safety limits of bone removal should be determined preoperatively to avoid the effects of bone morphological abnormalities.